New approach to Generate, Re-Generate, Encode, and Compress 3D structures using polynomial equations - Pal, Jimut Bahan; Nath, Asoke (International Journal of Computer Sciences and Engineering, 2018)
Almost every 3D objects can be represented with the help of a set of equations. When 3D objects are converted to text in terms of equations, any standard cryptographic techniques can be applied to encrypt it. This method is useful to hide classified military secrets, as we compress it to a large amount in the form of text, yet it can be regenerated in mathmod software, after decrypting it using the key. In this study, we propose a new way to formulate polynomial equation of any objects in context by fitting it using brute force techniques. We find that the complexity of the algorithm is too high to be achieved in practical scenarios, which encourages more efficient work in this new field.